A rational pharmacotherapeutic study of the prevalent prescription patterns of delamanid, ofloxacin, levofloxacin, and bedaquiline among the multi-drug resistant tuberculosis patients in global multi-centre tertiary care hospitals - Hazra, Moumita (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Delamanid, a nitro-dihydro-imidazooxazole, is a bactericidal cell wall methoxy-mycolic and keto-mycolic acids biosynthesis inhibitor in actively replicating, dormant, and intracellular tuberculosis, and both drug-susceptible and drug-resistant strains of M. tuberculosis and M. kansasii, decreasing hydrophobicity and facilitating better bacterial drug penetration. Delamanid promotes intracellular generation of microbiocidal nitrogen oxidative intermediaries including nitric oxide, toxic even to dormant M. tuberculosis. Ofloxacin, the racemic mixture and levofloxacin, the S-or levorotatory isomer of ofloxacin, are bactericidal to M. tuberculosis, MAC, M. fortuitum, and other atypical mycobacteria, with inhibitory effect on DNA gyrase, DNA topoisomerase IV and IL-1α, IL-6, IL-8. Bedaquiline, a novel diarylquinoline, inhibits mycobacterial adenosine triphosphate synthase of M. tuberculosis, disrupting mycobacterial energy metabolism and replication. Bedaquiline’s initial bacteriostatic action is followed by a bactericidal effect after 5-7 days. The objective was to perform a rational pharmacotherapeutic study of the prevalent prescription patterns of delamanid, ofloxacin, levofloxacin, and bedaquiline, among the multi-drug resistant tuberculosis patients, in global multi-centre tertiary care hospitals. Methods: A multi-centre, retrospective, observational and analytical study of clinical prescriptions of 100 multi-drug resistant tuberculosis patients in hospitals, were performed. For 24-48 weeks, these patients had been prescribed anti-tubercular drugs, like delamanid 100 mg and ofloxacin 400 mg twice daily, levofloxacin 750 mg and bedaquiline 400 mg once daily followed by 200 mg thrice weekly, as part of MDR-TB treatment regimens. The no. of prescriptions for each drug were recorded, and the corresponding prescription rates were statistically derived in percentages. Results: Delamanid was most commonly prescribed (32 prescriptions, 32%), followed by ofloxacin (29 prescriptions, 29%), levofloxacin (24 prescriptions, 24%), and bedaquiline (15 prescriptions, 15%). The completeness of the prescription contents, the dose of drug, the duration of treatment, the instructions of medication, the frequency of drug intake, the name of the drug and the dosage form of the drug were observed in 100% of prescriptions. Conclusions: Prescription frequency of delamanid was followed by ofloxacin, levofloxacin and bedaquiline. Prescription content analyses showed 100% completeness.